2017
DOI: 10.3390/nu9010027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resveratrol on Cognitive Performance, Mood and Cerebrovascular Function in Post-Menopausal Women; A 14-Week Randomised Placebo-Controlled Intervention Trial

Abstract: We tested whether chronic supplementation with resveratrol (a phytoestrogen) could improve cerebrovascular function, cognition and mood in post-menopausal women. Eighty post-menopausal women aged 45–85 years were randomised to take trans-resveratrol or placebo for 14 weeks and the effects on cognitive performance, cerebral blood flow velocity and pulsatility index (a measure of arterial stiffness) in the middle cerebral artery (using transcranial Doppler ultrasound), and cerebrovascular responsiveness (CVR) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
171
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(188 citation statements)
references
References 41 publications
3
171
0
14
Order By: Relevance
“…Most of the isoflavone studies were conducted in postmenopausal women, whereas resveratrol studies were evaluated in young and older adults of both genders, except for the study by Evans et al. , which was conducted in postmenopausal women only. Four studies showed that early postmenopausal women (less than 11 years since onset of menopause) gained cognitive benefits following soy isoflavone supplementation .…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Most of the isoflavone studies were conducted in postmenopausal women, whereas resveratrol studies were evaluated in young and older adults of both genders, except for the study by Evans et al. , which was conducted in postmenopausal women only. Four studies showed that early postmenopausal women (less than 11 years since onset of menopause) gained cognitive benefits following soy isoflavone supplementation .…”
Section: Discussionmentioning
confidence: 81%
“…Eight of the 23 studies in this review evaluated the effects of resveratrol or grape formulation on cognition with mixed outcomes . Kennedy et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, conflicting results [57, 58] and the lack of confirmation of several mechanisms involved in its activity in ‘preclinical’ models [52] preclude its current pharmacological use in patients with or at high risk of diabetes, or at high risk for development of cognitive impairment. However, recent clinical trials support the notion that resveratrol is capable of increasing cerebral blood flow during task performance [59, 49, 60] and enhancing oxygen extraction [49], reducing glycated hemoglobin A1c, preserving hippocampus volume, and improving hippocampus resting state functional connectivity in at-risk patients for dementia [61]. A randomized, double-blind clinical trial phase 1 (NCT02502253) will evaluate the effects of a Bioactive Dietary Polyphenol Preparation (BDPP), a combination of two nutraceutical preparations (grape seed polyphenolic extract, and resveratrol) in mood and cognition of patients with MCI and prediabetes or type 2 diabetes.…”
Section: Emerging Therapeutic Approachesmentioning
confidence: 99%